Online Authentic Materials For Learning English - Agnia Muti; Ezra Setiawan; Ida Oktaviani (International Multidiciplinary Conference on Social Sciences (IMCoSS), 2015)
Online authentic materials can be used for teaching English. This paper observes the use of some online authentic materials such as Edmodo, Podcast, and Instagram. It focuses on students’ motivation and skills in learning English by using those online authentic materials. The participants are students at the sixth semester, Teacher Training and Education Faculty, Bandar Lampung University. It is found that the students are motivated in learning English and there is improvement in speaking and writing skill. In addition, students’s comprehension in listening gets better.